Освітня складова проблем кадрового забезпечення ринку інформаційних технологій - Карп’як, А. О.; Рибицька, О. М.; Karpyak, A. O.; Rybytska, O. M. (Видавництво Львівської політехніки, 2005)
Досліджено проблеми недостатньої забезпеченості кваліфікованими кадрами українських ІТ підприємств та галузі в цілому. Проаналізовано взаємозв’язок регіональних показників кількості зайнятих у галузі фахівців та кількістю і якістю підготовки випускників формальної вищої освіти. Досліджувана проблема в найближчі роки тільки посилюватиметься з огляду на: зниження якості математичної підготовки у закладах середньої освіти, зокрема, пов’язаної з карантинними заходами, спричиненими пандемією COVID-19; руйнування освітньої інфраструктури у низці регіонів, спричиненого військовою агресією російської федерації на Україну та еміграція молоді шкільного віку. Обумовленість вибору дислокації ІТ-підприємства наявністю в регіоні достатньої кількості закладів формальної вищої освіти.

The problems of insufficient supply of qualified personnel for Ukrainian IT enterprises and the industry as a whole have been studied. The interrelation of regional indicators of specialists in the field of training and the quality of graduates of IT specialties of formal higher education is analyzed. The studied problem in the coming years will be exacerbated by: reducing the quality of mathematical training in secondary education, in particular related to quarantine measures caused by the COVID-19 pandemic and the destruction of a significant part of the infrastructure, including an educational infrastructure in a number of regions of Ukraine caused by the military aggression of the Russian Federation, as well as the forced emigration of school-age youth. The connection between the availability of a sufficient number of specialists in the specialty and the number of high-quality institutions of higher education that provide specialized educational services in the reagion is analyzed. The proposals to the heads of IT enterprises and institutions of higher education, which train future IT specialists, unite projects, are substantiated, namely: to create joint centers for the development and updating of curricula and programs; to conduct free refresher courses for scientific and pedagogical workers; to create laboratories for high-quality information support of the educational process; to provide financial support to the technical base of the institutions of higher education. These measures can enhance the provision of quality educational services through integration, rather than coexistence, of formal and non-formal education. Reforming specialized higher education is becoming an urgent need. Success requires the involvement of practitioners in the educational process on the one hand and the involvement of research and teaching staff in the development of projects occupied by IT companies in the region. The top management of the companies with the highest qualification for staffing all age categories of the IT market of Ukraine needs to monitor the feasibility of investments in the development of non-formal "post-academic" education and pay attention to the need to involve educators from the basic level. The results of the study indicate low labor mobility. The vast majority of graduates of IT specialties are looking for a job in the regions where they received higher education, or move to the capital Kyiv. The only exception among all regional centers in the city of Ternopil. Based on the analysis, recommendations for the top management of Ukrainian IT companies are formulated. In case you need to quickly increase the size, the most attractive is Kyiv and Lviv. However, the location in Kyiv is a competitive environment that affects the high cost of doing business. As a result of the large-scale invasion and destruction by the Russian occupiers of KhNU. Karazin and a number of other educational institutions, in the coming years the widespread development of IT business in the Kharkiv region is becoming unpromising. The authors of the study suggest that IT business management should pay special attention to Ternopil. In Ternopil, due to the activities of the IT cluster and its cooperation with the Free Economic Zone, the number of IT specialists is quickly increasing and low competition between companies leads to a lower cost of doing business.
An educational component of the personnel support problems of the information technologies market
Keywords: ІТ-підприємство; ІТ-фахівець; галузь інформаційних технологій; менеджмент; підприємство; формальна освіта; неформальна освіта; регіональний розвиток; IT enterprise; IT specialist; information technology industry; management; enterprise; formal education; non-formal education; re; 005.511; 303.722.4